Analysis of the Effect of Frequency Weighting According to the Sperling Index Method on the Dynamic Response of the Railway Vehicle Carbody to Vertical Vibrations - Ioana Izabela Apostol; Mădălina Dumitriu; Traian Mazilu (Applied Sciences)
The topic of the paper is part of the research area in which the methods of ride comfort evaluation are investigated, to identify their advantages and limitations, the correlation of the comfort indices obtained by different methods, and even the improvement of these methods as an application methodology or as an interpretation. In this paper, the Sperling index method is analyzed from a new perspective, specifically, the effect that the frequency weighting functions specific to this method have on the dynamic response of the railway vehicle carbody, as evaluated by the power spectral density (PSD) of the acceleration. The analysis is based on numerical simulation results for three different cases: respectively, the unweighted PSD of the acceleration, the frequency-weighted PSD of the acceleration with the function for the evaluation of ride quality (RQ)and the weighting function for the evaluation of ride comfort (RC). The applications for the numerical simulation are based on an original vehicle–track system model with 15 degrees of freedom, which includes a rigid–flexible coupled model of the vehicle and the equivalent model of the track. This model considers important elements that can influence the vertical vibration behavior of the carbody, namely, the carbody structural flexibility, which is represented by an equivalent Euler–Bernoulli beam, the system through which the longitudinal forces are transmitted from the bogies to the carbody, and the elasticity of the wheel–rail contact. Based on the analyses developed in the paper, the relevant conclusions regarding the effect of the frequency weighting functions specific to the Sperling index method on the dominant vertical vibration modes of the carbody are synthesized. These conclusions are correlated with the results of the Wz index for the RQ evaluation and the RC evaluation.